Patients’ over-visit phobia versus physician’s over-prescription phobia - Shanmugam, Ramalingam (International Journal of Research in Medical Sciences, 2018)
Background: Hospital administrators conduct survey of patients to solicit their satisfactions and/or concerns for accreditation or renewal of license. For the first time in the literature, this article defines and illustrates the existence of patient’s over-visit phobia and the physician’s over-prescription phobia. These phobias pave way to formulate policy to increase hospital’s efficiency. Methods: The number, of times a patient visits the physician (with a visitation rate) and the number, of prescriptions written by a physician (with a prescription rate) are assumed to follow Poisson type probability patterns. This article, in a novel manner, untangles intricacies and inter-relations of these two phobias. Results: An analysis of the Australian Health Survey data, using our model and methodology, estimates visit and prescription rate to be and respectively. The chance for patient’s visit phobia and physician’s prescription phobia is respectively 0.33 (with a reluctance level 2.16 to make additional visits) and 0.46 (with an avoidance level 3.17 to prescribe more medicines). Conclusions: A few comments and suggestions are stated to save service time/cost for the sake of more hospital’s efficiency. With a methodology in this article, level of over-visits by the patients and the level of over-prescriptions by the physicians are estimable to reduce the waste of hospital’s resources.